2011
DOI: 10.1111/j.1365-3156.2011.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre prospective study on dengue classification in four South‐east Asian and three Latin American countries

Abstract: Summaryobjective To evaluate the existing WHO dengue classification across all age groups and a wide geographical range and to develop a revised evidence-based classification that would better reflect clinical severity.methods We followed suspected dengue cases daily in seven countries across South-east Asia and Latin America and then categorised them into one of three intervention groups describing disease severity according to the overall level of medical and nursing support required. Using a pre-defined ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 23 publications
7
180
0
10
Order By: Relevance
“…Several studies [10,13,14] reported that the revised WHO classification is more sensitive as well as more or comparably specific in identifying severe cases. In contrast, some still indicate that WHO 1997 is more sensitive -though less specific -in capturing severe cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [10,13,14] reported that the revised WHO classification is more sensitive as well as more or comparably specific in identifying severe cases. In contrast, some still indicate that WHO 1997 is more sensitive -though less specific -in capturing severe cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…4 The elucidation of clinical profile is very important for patient management and thus crucial for saving life. Due to limitations of World Health Organization (WHO) 1997 dengue classification guidelines WHO revised their guidelines in 2009 5 and accordingly the clinical classification was revised as dengue without warning signs, dengue with warning signs, and severe dengue which was much easier to understand. [6][7][8] The present study is an attempt to describe the salient clinical as well as laboratory findings of serologically confirmed hospitalized cases of dengue fever.…”
Section: Introductionmentioning
confidence: 99%
“…10 Classicamente as formas clínicas eram divididas em febre da dengue, febre hemorrágica da dengue e síndrome de choque da dengue. A OMS propõe uma nova classificação com duas categorias: dengue (com ou sem sinais de alerta) e dengue grave, seguindo alguns critérios 4,11,12 ( Fig. 1).…”
Section: Resultsunclassified